Mandibular canal versus inferior alveolar canal: A Delphi study. Issue 7 (5th May 2021) - Iwanaga, Joe; Ibaragi, Soichiro; Takeshita, Yohei; Asaumi, Junichi; Horner, Keith; Gest, Thomas R.; Tubbs, R. Shane
Abstract: The general principles of anatomical terminology indicate that the "mandibular canal" should be named the "inferior alveolar canal" as it accommodates the inferior alveolar neurovascular bundles. Therefore, we performed a Delphi study to evaluate the current understanding and use of the terminology in different geographical regions and areas of expertise and to determine the appropriate terminology for this bony canal. A Delphi panel was formed and questions sent and answered via email about: field of expertise (anatomy, oral surgery/oral and maxillofacial (OMF) surgery, oral radiology/OMF radiology, plastic surgery, ENT surgery, or dentistry with the exception of oral/OMF surgery and oral/OMF radiology), years of experience in the field of expertise, country currently working in, "what is the name of the bony canal that contains the inferior alveolar neurovascular bundle, " and "what should the structure above be called, in general?" A total of 52 participants responded to the questionnaire. Half or more of the experts in anatomy, oral/OMF surgery, and ENT/plastic surgery considered "mandibular canal" to be the most appropriate name for this bony canal. In contrast, more than half of all experts in oral/OMF radiology and dentistry, that is, most fields of dentistry, considered "either mandibular canal or inferior alveolar canal" to be the appropriate name. The results of the Delphi study and general principles suggest that an alternative term for the "mandibular canal" should be "inferior alveolar canal."